Gender differences in Meiteiron - Pramodini, N. (2024)
This article explores the gender dominance and differences in Meiteiron in some detail with a modest historical explanation. The lin-guistic evidence argues against the general claim of prior male domi¬nance, particularly the linguistic evidence in archaic Meiteiron. It is argued that the speech of women was not considered inferior, a reflec¬tion of the high status women held in pre-Hindu Meitei society. Although there are decidedly matriarchal elements in the modern lan¬guage, present day Meitei society is very much male dominated